The analysis of the influence of xanthan gum and apple pectins on egg white protein foams using the large amplitude oscillatory shear method. (March 2016) - Ptaszek, Paweł; Kabziński, Maciej; Ptaszek, Anna; Kaczmarczyk, Kacper; Kruk, Joanna; Bieńczak, Agata
Abstract: This research study analysed the rheological properties of fresh food foams based on egg white protein, and with the addition of apple pectins and xanthan gum. The rheological analysis was carried out using the large amplitude oscillatory shear (LAOS) technique. From the obtained results two types of Lissajous figures were constructed, describing the elastic and viscous properties. The obtained figures were subjected to geometrical decomposition, which resulted in the determination of the stress values characteristic of nonlinear purely elastic and purely viscous properties. The Fast Chebyshev Transform allowed for the calculation of the Chebyshev coefficients, and further detailed analysis of rheological behaviour of foams as a function of strain amplitude. The determination of the values of elastic and viscous Chebyshev coefficients allowed for the interpretation, with high resolution, of nonlinear rheological properties of the obtained foams. Graphical abstract: Highlights: LAOS measurements were done for wet foams. Geometrical decomposition of Lissajous figures was done. Synergistic effects have been observed in the foams with xatnthan gum and pectin.